The Impact of Zakat Distribution and Open Unemployment Rate on Economic Growth in Indonesia - Alfina Nur Azzahra; Ferry Khusnul Mubarok; Rofiul Wahyudi; Khairulman Akbar Hutagalung (Green Economics Review, 2025)
Economic growth is a key indicator of development performance, reflecting increases in per capita output and overall societal welfare. Despite Indonesia’s relatively stable economic growth, the effectiveness of socio-religious instruments such as zakat in promoting macroeconomic growth remains subject to debate, particularly when examined alongside labor market challenges as reflected in the Open Unemployment Rate (OUR). The novelty of this study lies in its empirical assessment of the role of zakat distribution and unemployment in influencing economic growth at the provincial level, thereby providing a more nuanced understanding of regional economic dynamics in Indonesia. This study aims to analyze the impact of zakat distribution and the Open Unemployment Rate on Indonesia’s economic growth. A quantitative approach is employed using multiple linear regression analysis. The study utilizes secondary data covering 34 provinces in Indonesia, obtained from the national statistical authority and officially recognized zakat management institutions. The findings reveal that zakat distribution does not have a positive and statistically significant effect on economic growth. Similarly, the Open Unemployment Rate does not exhibit a statistically significant negative effect on economic growth. These results suggest that the contribution of zakat to macroeconomic growth has not yet been optimal. This condition may be attributed to the relatively limited scale of zakat distribution, the predominance of consumptive-oriented allocation, and the lack of integration between zakat management and broader economic development policies. The implications of this study highlight the importance of strengthening zakat governance through the expansion of productive zakat programs and enhancing policy synergy between zakat institutions, labor market strategies, and national economic development frameworks. Such integration is expected to improve the effectiveness of zakat as an instrument for fostering inclusive and sustainable economic growth.